Environmental factors that influence species diversity of floodplain plant communities in different flooding phases in the Okavango Delta, Botswana - Tsheboeng, Gaolathe; Bonyongo, Mphaphi; Murray-Hudson, Mike (Bothalia, 2020)
Background and objectives: Species composition and distribution in seasonal floodplain plant communities are influenced by variation in flooding. However, the influence of intra-flooding variation phases on the diversity of seasonalfloodplain plant communities has not been studied in the Okavango Delta. The objective of this study was to investigate environmental factors that influence species composition and distribution of seasonal floodplain communities beforeand after flooding. It was hypothesised that environmental factors that influence the species composition and distribution in seasonal floodplain communities will vary with intra-flooding seasons.Methods: Flooding depth was measured in May (before flooding) and September (flood recession/after flooding) in forty 25 m2 plots. Flooding duration was recorded as the number of weeks in which the plots were inundated. The soil was sampled before and after floods and analysed for pH, extractable P, K, Mg, Ca and Na. Plant identification and estimation of percentage cover were done in the 25 m2 plots in which environmental variables were sampled. The relationshipbetween environmental variables and seasonal floodplain plant community composition and distribution was sought using Non-metric Multi-dimensional Scaling. Paired Student’s t test was used to compare the means of environmentalvariables before and after flooding.Results: Factors that influenced the distribution of species before flooding were Na, K, water depth and flooding duration. After flooding, the factors that influenced species composition and distribution were K, Na, Mg, pH, water depth and flooding duration.Conclusion: These results suggest that during flooding K and Mg are deposited in the floodplains due to lateral water flow. Our results also suggest that any water abstraction from the Okavango River Basin should take into consideration theimportance of flooding duration and depth in sustaining species composition and distribution of seasonal floodplain plant communities so that such developments do not disturb the ecological functioning of the Delta.